Optimalisasi Literasi Digital untuk Mencapai Pendidikan Berkualitas Menuju Sustainable Development Goals (SDGs) 2030 - Stevani, Awanda Mella; Nugraheni, Nursiwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research discusses the importance of digital literacy in efforts to improve quality education for human resources, which influences achieving the Sustainable Development Goals. This research aims to understand the importance of digital literacy and to find out strategies that can be used to maximize digital literacy for the nation's generation. The research method used is the literature study method, and descriptive analysis by collecting literature, books and other sources that are relevant to the research topic to conclude. The results of this research show that the Sustainable Development Goals or SDGs are a program that is interconnected and influences each other in achieving sustainable development. The role of digital literacy is to form a more critical individual mindset, increase creativity and increase extensive knowledge so that it can influence a person's quality. Maximizing digital literacy has several influencing factors, the most important of which is the role of the government which is in control and supports in improving the quality of education. In increasing digital literacy, of course, utilizing existing technology, technology can be a means of developing technological skills so that you become an individual who is capable and can master technology well. By using technology in education, students can be formed who have the skills, knowledge and broad insight to contribute to the success of sustainable national development.